Dominant features and negative trends in the current World Taekwondo Federation (WTF) competition system - Moenig, U. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2017)
Background. The introduction of the Protector and Scoring System (PSS) laid to rest, accusations of game manipulation in WTF sport taekwondo and ended disputes regarding scoring decisions; but, at a significant cost. Problem: The current WTF taekwondo competition system, with the PSS as its core feature, has given rise to a variety of strikingly negative trends, such as the overreliance on weak, stationary kicking techniques with the front leg, a preference for relatively tall and lean but less athletic competitors, and the appearance of a variety of unconventional, and sometimes bizarre scoring techniques. This article will argue that these characteristics are interrelated and largely the result of the hurried, unmanaged introduction of the PSS, which turned taekwondo competition from a full-contact combat sport into a partly light-contact, points game. Aim. This article aims to encourage a discussion about the fundamental soundness of and necessity for the PSS. Methods. Since the topic of this article lacks broad scientific research and empirical data, the methodology of this article relies largely on an analysis of deductions, and is based on a literature review, personal experience, conversations, and observations. Results and conclusion. On a positive note, today`s taekwondo leadership has finally acknowledged how the quality of taekwondo sparring and competitions has worsened, although it remains to be seen whether or not the WTF can fix the problem.